Maternal and child health care services: prevention of complications, reduction of maternal, neonatal and child morbidity and mortality rate: A narrative review - Vilma Ajijul Jana (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Maternal and child health (MCH) services are critical interventions that improve maternal and child health outcomes globally. Purpose: To review maternal and child health services: prevention of complications, reduction of maternal, neonatal, and child morbidity and mortality rates: Narrative review Method: A narrative review method was used to synthesize current evidence on effective MCH interventions. Results: Evidence from global and regional literature highlights effective interventions including antenatal care, skilled birth attendance, emergency obstetric care, postnatal care, immunization, and nutrition programs. Conclusion: The need for strengthened health systems, community participation, and policy support is emphasized to achieve Sustainable Development Goals (SDGs) 3.1 and 3.2. Suggestion: Implementing frequent CHW home visits is vital in the Prevention of Complications, Reduction of Maternal, Neonatal and Child Morbidity and Mortality Rate. Aim for multiple visits during both antenatal and postnatal periods, as the strongest neonatal mortality reduction (24%) occurred in studies with ≥ 3 visits and integrated antenatal plus postnatal care, Package interventions into comprehensive home-based care